Impact of lactoferrin supplementation on cotrimoxazole pharmacokinetics: A preliminary clinical investigation - Dion Notario; Angela Marietha Munzir; Yulina Novella; Linawati Hananta (International Association of Physical Chemists (IAPC), 2024)
Background and Purpose: Cotrimoxazole, a commonly prescribed antibiotic, has substantial resistance, especially in Indonesia, with its uropathogenic resistance reaching 67% in 2017. Although cotrimoxazole has been suggested to be co-administered with lactoferrin to enhance its antibacterial effectiveness and this practice has been widely adopted since the Covid-19 pandemic, the impact of lactoferrin on the pharmacokinetics of cotrimoxazole remains relatively unknown. This study aims to conduct a preliminary clinical investigation into the impact of lactoferrin supplementation on the pharmacokinetics of cotrimoxazole, focusing on the elimination rate and excretion of unchanged drug in urine. Experimental Approach: This study employed a blinded, cross-over, single-dose pharmacokinetics investigation, which included five healthy volunteers as participants. In the initial period, the first group received cotrimoxazole (80 mg trimethoprim and 400 mg sulfamethoxazole) along with a lactoferrin-containing supplement, while the second group only received cotrimoxazole. Subsequently, after a washout period, the conditions were reversed. Urine sampling was conducted at intervals from 0 to 24 hours post-medication, and drug levels in the urine were determined using high-performance liquid chromatography. Key Results: The population-based pharmacokinetic analysis revealed that the optimal model was the one-compartment model with first-order elimination and proportional residual error. Conclusion: The findings show that the administration of lactoferrin-containing supplements did not significantly influence the covariate model and, therefore, did not alter the pharmacokinetics parameter of cotrimoxazole in urine with a single administration, implying that lactoferrin did not cause drug interaction problems when given simultaneously.